Tang Luo Ning, a Traditional Chinese Compound Prescription, Ameliorates Schwannopathy of Diabetic Peripheral Neuropathy Rats by Regulating Mitochondrial Dynamics In Vivo and In Vitro - Zhu, Jiayue; Yang, Xinwei; Li, Xiao; Han, Shuo; Zhu, Yanbo; Xu, Liping (Frontiers in Pharmacology, 2021)
Tang Luo Ning recipe (TLN), a traditional Chinese compound prescription, has been used clinically to treat diabetic peripheral neuropathy (DPN) in China, however, the exact mechanisms remain unclear. The objective of this study is to unravel the effects of TLN on mitochondrial dynamics of DPN in vivo and in vitro. Mitochondrial function was determined by Ca2+ and ATP levels of streptozotocin (STZ) induced DPN rats and mitochondria structure, mitochondrial membrane potential (MMP), mtDNA of high glucose incubated SCs. Mitochondrial dynamics protein including Mitofusin 1(Mfn1), Mitofusin 2 (Mfn2), optic atrophy 1 (Opa1) and dynamin-related protein 1 (Drp1) were investigated using Western blot or immunofluorescence. Myelin basic protein (MBP), myelin protein zero (MPZ or P0) and sex determining region Y (SRY)-box 10 (Sox10) and were measured to represent Schwannopathy. Our results showed that TLN increased ATP levels, MMP and mtDNA while decresed Ca2+ to improve mitochondrial function of in vivo and in vitro. To maintain balance of mitochondrial dynamic, TLN reduced the mitochondria number while increased the mitochondria coverage, mitochondrial network size and branch length. Further, mitochondrial dynamics related Mfn1, Mfn2, Opa1 were increased while the Drp1, phosphorylated Drp1 and Drp1 located in mitochondria were decreased after treatment with TLN. Additionally, TLN improved Schwannopathy by increasing MBP, Sox10 and P0 expressions. In conclusion, our study indicated that TLN’ s function on DPN may link to the improvement of the mitochondrial dynamics which provides scientific evidence for the clinical application.